2015
DOI: 10.1007/s11481-015-9623-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lupeol Against Lipopolysaccharide-Induced Neuroinflammation via the p38/c-Jun N-Terminal Kinase Pathway in the Adult Mouse Brain

Abstract: Recent studies have demonstrated a close interaction between neuroinflammatory responses, increased production of inflammatory mediators, and neurodegeneration. Pathological findings in neurological diseases such as Alzheimer's disease, Parkinson's disease, and Huntington's disease have shown common signs of neuroinflammation and neurodegeneration. Lupeol, a natural pentacyclic triterpene, has revealed a number of pharmacological properties including an anti-inflammatory activity. This study aimed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 61 publications
4
65
0
2
Order By: Relevance
“…which stay in good agreement with its previous findings [51]. However, lupeol treatment significantly attenuated Aβ induced oxidative-nitritive stress and decreased the levels of pro-inflammatory cytokines, confirming its antioxidant and antiinflammatory properties [52].…”
Section: Archivos De Medicina Issn 1698-9465 Journal Of Neurology Andsupporting
confidence: 92%
“…which stay in good agreement with its previous findings [51]. However, lupeol treatment significantly attenuated Aβ induced oxidative-nitritive stress and decreased the levels of pro-inflammatory cytokines, confirming its antioxidant and antiinflammatory properties [52].…”
Section: Archivos De Medicina Issn 1698-9465 Journal Of Neurology Andsupporting
confidence: 92%
“…Systemic administration of LPS evokes inflammatory processes in the body, which cause detrimental effects on the brain and other vital organs. In vitro and in vivo studies demonstrated that LPS induced inflammation via the up-regulation of different proinflammatory mediators, such as nitric oxide species (NOS), prostaglandin E2 (PGE2), and cyclooxygenase (COX)-2, and proinflammatory cytokines, including interleukin-1 (IL-1), IL-6, and tumor necrosis factor-α (TNF-α) 1 2 3 .…”
mentioning
confidence: 99%
“…Toll-like receptors (TLRs) play important roles in the sensing of body pathogens and macrophages and the initiation of immune responses. LPS is primarily recognized by the CD14/TLR-4 receptor complex, which is expressed on microglia and astrocytes in the CNS 1 4 5 . The downstream signal transduction of this receptor complex activates the TLR4/nuclear factor (NF)-κB pathway, which leads to the generation of inflammatory mediators and the production of neuroinflammation and neurodegeneration 6 7 .…”
mentioning
confidence: 99%
“…In agreement with our observations, accumulating evidence indicates that the p38 and JNK/c-Jun pathways are involved in the regulation of the expression of TNF-α. However, although investigators tried to identify the mechanisms responsible for the suppression of the expression of TNF-α in astrocyte, this work did not extend to PGE 2 and PGI 2 [ 50 - 54 ]. This is not the first time we have demonstrated the involvement of the p38 and JNK/c-Jun pathways in regulating the expression of TNF-α; however, we extended these mechanisms to include the roles of PGE 2 and PGI 2 in regulating the synthesis of TNF-α.…”
Section: Discussionmentioning
confidence: 99%